Soul, Not Mind, Out There in the World Platonic Inclinations in Reading Wittgenstein - Beran, Ondřej (WALTER DE GRUYTER GMBH, 2024)
The paper comments on the later Wittgenstein’s conception of the soul. While Wittgenstein touches on the issue of the soul in connection with the debates of the body and the mind and of behaviorism, I lean towards those who read his account independently, as exploring a key concept in understanding what makes life a human life, that is, one in which the dimension of morality features centrally. This interpretation would bring Wittgenstein close to Plato; some Wittgensteinian philosophers (such as Rhees or Gaita) offer readings of the two philosophers along analogous “ethical” lines. The distinction between the mind and the soul reveals itself most clearly in the context of the difference between the deterioration of the mind (mental disorders) and the deterioration of the soul. Disorders of the soul appear to be problems of life, often with moral stakes. Examples of ailments of the soul are discussed, e. g., environmental grief.
Duše, nikoli mysl; venku ve světě
Keywords: Soul; Mind; Wittgensteinian Ethics; duše; mysl; wittgensteinovská etika